Pengaruh Perkembangan Penerimaan Zakat Sebagai Instrumen Kebijakan Fiskal Terhadap Perkembangan Penerimaan Negara Indonesia - Sofi Faiqotul Hikmah (JPSDa: Jurnal Perbankan Syariah Darussalam, 2023)
Quantitative research entitled “The Influence of the Development of Zakat Acceptance as an Instrument of Fiscal Policy on the Development of Indonesian State Revenue” is a quantitative research whose data is obtained from the official website of BAZNAS (National Amil Zakat Agency) which is a financial report published annually, besides that the author also took secondary data from BPS (Central Statistics Agency) Ministry of Finance of the Republic of Indonesia and analyzed using simple linear regression manually or with the help of Microsoft Excel. The results showed that the development of zakat receipts from 2010-2021 continued to increase even though in 2020 Indonesia was hit by the Covid-19 pandemic, even the development of zakat receipts from year to year was never below 10%, while the development of state revenues experienced fluctuations, sometimes has increased, sometimes it has also decreased, especially during the Covid-19 pandemic. The results of manual data processing using a simple linear regression formula can be seen that the value of F Count < F Table because 0.00 < 4.965, it can be concluded that variable X (Development of Zakat Receipts) has no effect on variable Y (Development of Tax Receipts).